CD5 positive hairy cell leukemia: A rare case report with brief review of literature. Issue 5 (30th April 2016) - Jain, Dharmendra; Dorwal, Pranav; Gajendra, Smeeta; Pande, Amit; Mehra, Simmi; Sachdev, Ritesh
Abstract : Objective: The aberrant expression of CD5 in both HCL and HCL‐v is a very rare event. Although a number of CD5 positive HCL and HCL‐v cases have been reported, but these are far and few in between. We aimed to review the reported cases of CD5 positive HCL and its variant. Method: We hereby report a case of CD5 positive HCL, with variations in PIK3CA and PDGFRA gene, along with a brief review of literature of the cases of CD5 positive HCL and its variant. Results and Conclusion: The current case was positive for CD103, CD11c, CD25, and CD123 which has led the diagnosis to be of typical HCL. With the extensive literature review we found that only 26 cases of hairy cell leukemia [HCL and HCL‐v] bearing CD5 expression have been reported so far. The positivity of CD5 is more common in HCL‐v as compared to HCL. Additional prospective studies of CD5+ HCL and its variants are required to show whether they are a clinically significant subgroup of lymphoid malignancies. © 2016 International Clinical Cytometry Society